2001
DOI: 10.1136/adc.84.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Influences of ethnicity on perinatal and child mortality in the Netherlands

Abstract: Aims-To investigate the diVerences in perinatal death and child mortality between diVerent ethnic groups in the Netherlands. (Arch Dis Child 2001;84:222-226) Methods-Retrospective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
3
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 17 publications
5
52
3
2
Order By: Relevance
“…Our examination of the underlying ICD-codes suggested that hereditary disorders made up about a 1/3 of all events among other death causes. This is similar to Schulpen et al 10,14 who found that inherited congenital conditions were one of the main causes of the excess risk of mortality among Turkish and Moroccan preschool children. It has been show that advanced paternal age is associated with an increased rate of congenital malformations and other severe diseases (e.g.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our examination of the underlying ICD-codes suggested that hereditary disorders made up about a 1/3 of all events among other death causes. This is similar to Schulpen et al 10,14 who found that inherited congenital conditions were one of the main causes of the excess risk of mortality among Turkish and Moroccan preschool children. It has been show that advanced paternal age is associated with an increased rate of congenital malformations and other severe diseases (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the limited amount of studies on this research topic, our findings are comparable to results from a Dutch study on ethnic differences in early and late child mortality (0-15 years) 10 , finding Turkish and Moroccan children with twice as high a death rate as native Dutch children. In the 1-4 year old children hereditary disorders and external causes largely contributed to the ethnic differences.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Descriptive epidemiological data on injury incidence and mortality from the Netherlands (e.g., Schulpen, van Steenbergen, & van Driel, 2001;Stirbu, Kunst, Bos, & van Beeck, 2006;van der Wal & Pauw-Plomp, 1996) have consistently showed that ethnic minorities, particularly those of Turkish and Moroccan origin, have a higher drowning mortality rate than the indigenous Dutch. For example, in a study developed to explore ethnic differences in injury related mortality in the Netherlands, Stirbu et al (2006) reported that ethnic minority group members (i.e., Turkish, Moroccan, Surinamese, and Antilleans), and males in particular had an increased mortality rate from drowning accidents, even when adjusting for age, income, and place of residence (urban vs. rural).…”
Section: Statistical Data On Ethnic and Racial Minorities' Drowning Rmentioning
confidence: 99%
“…For example, in a study developed to explore ethnic differences in injury related mortality in the Netherlands, Stirbu et al (2006) reported that ethnic minority group members (i.e., Turkish, Moroccan, Surinamese, and Antilleans), and males in particular had an increased mortality rate from drowning accidents, even when adjusting for age, income, and place of residence (urban vs. rural). Likewise, in a study developed to explore the influence of ethnicity on child mortality in the Netherlands, Schulpen et al (2001) indicated that youth of Turkish and Morrocan heritage had a higher mortality rate from drowning accidents compared with native-born children.…”
Section: Statistical Data On Ethnic and Racial Minorities' Drowning Rmentioning
confidence: 99%